Palladium-Catalyzed Oxidation of Indoles to Isatins by tert-Butyl Hydroperoxide - Luo, Junfei; Gao, Shanshan; Ma, Yaorui; Ge, Guoping (Synlett, 2018)
The combination of a Pd catalyst and tert-butyl hydroperoxide (TBHP) is a powerful catalytic system for many types of oxidative transformations. Here, we report that a Pd/TBHP system facilitates the oxidation of indoles with a range of functionalities to give the corresponding isatin derivatives in good yields.
Keywords: palladium catalysts; butyl hydroperoxide; oxidation; indoles; isatins